Evaluation of Usability Aspects of Consumer Products in Online Sales - Razza, Bruno; Paschoarelli, Luis Carlos [UNESP] (Elsevier, 2015)
An increasing number of sales are currently being made over the telephone or Internet. In this kind of shopping, consumers cannot touch, hear, smell, feel the weight or handle the products before buying them, and as a result, the buying decision is made based exclusively on the visual sense. In this context, consumers come to rely on other aspects of the product, such as brand, price, vendor reliability and feedback from other consumers rather than intrinsic qualities of the product, such as colour, shape, weight, smell or texture. Despite the sight being predominant in humans, it is unclear to what extent users can estimate quality of use only from looking at the product. This study aimed to investigate which product features led users to make judgments about aspects of usability using disposable razors as a case study. Thus, a system simulating a virtual store was developed in which the user evaluated usability aspects of disposable razors through the observation pictures. Forty disposable razors commonly found in the international market were employed. The study recruited 321 adult men non-paid volunteer; their mean age was 30.5 years [± 10.81], ranging from 18 to 66; All subjects were users of disposable razors. Thirteen dimensions of usability of razors were evaluated with a 7 points Likert scale. The data evaluation consisted of identifying correlation between the product features obtained from Morphological Analysis and the evaluation of usability. For this, Multiple Linear Regression was used in StatSoft Statistics R7 software; values above 0.7 were considered as high correlation and values above 0.4 as moderate correlation. The results showed no high correlation in the sample. Moderate correlations, however were found in only 6 usability criteria. However, there seems to be a cross-influence of razors’ intrinsic characteristics, making it difficult to isolate one specific feature. Future studies should investigate the perception of usability when the product is effectively used, i.e. with all sensory modalities integrated.
Keywords: Disposable Razors.; Multiple Linear Regression; Sensory Perception; Usability; User Experience